Studi Komparasi Perhitungan Return Deposito Syari’ah di BSM dengan Deposito Konvensional di Bank Mandiri - Syaparuddin Syaparuddin (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2015)
This  study  aims  to  find  out:  (1)  the  calculating  methode  of time-deposit return in BSM and  Bank Mandiri, and (2) if BSM or Bank Mandiri gives a better time-deposit return to itself and its customers. The result of this study showed that  the return of BSM is  higher  than that of Bank Mandiri. However, the profit which BSM gets is uncertain because the return which will be given to its customers depends on the income of BSM  which  gets.  It  means  that  the  return  of  mudhârabah  time-deposit which  BSM  gives  to  its  customers  is  uncertain,  whereas  the  return  of time-deposit  which  Bank  Mandiri  gives  to  its  customers  is  certain  and almost no any risk will appear.  But if the risk of that is lower, its return will be lower too. If it is so, the public will no get a high profit if they avoid any risk, because the higher return they  will expect, the higher risk they  will  face. Risk and return always have a positive relationship. If the public understand this problem, they will choose the Islamic Bank (BSM) to deposit their money. Abstrak:  Penelitian  ini  bertujuan  (1)  un